Pengembangan Makanan Enteral Tinggi Energi Tinggi Protein Berbasis Telur Bebek, Labu Kuning, dan Tempe (BELATE) - Rahmawati, Seruni; Mustikaningrum, Fitriana (Ghidza: Jurnal Gizi dan Kesehatan, 2025)
High-energy high-protein (HEHP) diets are essential to support the recovery of patients at risk of malnutrition. However, lactose-reduced HEHP enteral formulas are still rarely available in hospitals, despite the fact that many patients experience lactose intolerance. This condition can lead to digestive discomfort when consuming milk-based formulas. To address this issue, researchers developed a blenderized enteral formula using local ingredients—pumpkin, tempeh, and duck eggs—called BELATE, which is naturally low in lactose. This study aims to describe the physical quality, estimated nutritional content, flow rate, and viscosity of the BELATE formula, as well as assess its sensory acceptability. Methods: This was an experimental study with a descriptive approach. The BELATE formula was analyzed for its estimated nutritional composition, viscosity, energy density, flow rate, and production cost. Sensory evaluation was conducted using a paired t-test. In 1000 ml, the BELATE formula provides 1036.3 kcal with 31.5 g of protein (12.2%), 42.5 g of fat (36.9%), and 133.3 g of carbohydrates (51.5%), resulting in an energy density of 1.03 kcal/ml. The viscosity was measured at 23.43 cP, with osmolality of 352 mOsm/kg. Flow rate tests showed 1.13 ml/sec using a 12 Fr tube and 1.78 ml/sec with a 14 Fr tube. Overall, the BELATE formula was well accepted, with an average organoleptic score of 3.87 ± 0.64. The BELATE enteral formula, made from duck eggs, pumpkin, and tempeh, meets the recommended standards for HEHP enteral nutrition in terms of viscosity, osmolality, and energy density, and it is well received by panelists.